Pengaruh Pengendalian Internal, Moralitas Individu dan Budaya Organisasi terhadap Kecenderungan Kecurangan Akuntansi Pemerintah Desa - Ike Abdi Nurjanah; Mia Angelina Setiawan (Universitas Negeri Padang, 2021)
This study aims to examine the effect of internal control, individual morality, and organizational culture on the tendency of accounting fraud. The population in this study were 51 villages in Dharmasraya Regency. The sampling method used is the total sampling method. Total sampling is a sampling technique where the number of samples is the same as the population. In this study, the data source used is the primary data source. Data collection techniques in this study using a questionnaire. The results of this study indicate that internal control and organizational culture have no effect on the tendency of accounting fraud and individual morality has a positive and significant effect on the tendency of accounting fraud.